2010
DOI: 10.1097/phm.0b013e3181c9fa9d
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Intervention Research on Persons with Disabilities

Abstract: The purpose of this article was to provide a comprehensive review of the exercise intervention literature on persons with physical and cognitive disabilities. Electronic searches were conducted to identify research articles published from 1986 to 2006. Of the 80 physical activity/exercise interventions identified in the literature, only 32 were randomized controlled trials. The remaining studies were nonrandomized controlled trials with (n = 16) and without (n = 32) a control group. There was a mixture of exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(97 citation statements)
references
References 83 publications
2
94
0
1
Order By: Relevance
“…Physical activity intervention research design should be based on established behavior theory, particularly conceptualization of the problem and defining the target behavior that will be modified. 17,44 An increase in the number of randomized control trials is needed, 14 but studies using this design must address quality control in design and reporting to ensure usability of findings. 15,17 Finally, there are many challenges to conducting large-scale interventions in youth with intellectual disabilities, so researchers are encouraged to develop multi-site collaborative projects to increase sample size, strengthen research design and improve generalizability of findings.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity intervention research design should be based on established behavior theory, particularly conceptualization of the problem and defining the target behavior that will be modified. 17,44 An increase in the number of randomized control trials is needed, 14 but studies using this design must address quality control in design and reporting to ensure usability of findings. 15,17 Finally, there are many challenges to conducting large-scale interventions in youth with intellectual disabilities, so researchers are encouraged to develop multi-site collaborative projects to increase sample size, strengthen research design and improve generalizability of findings.…”
Section: Discussionmentioning
confidence: 99%
“…The recommendations for PA comprise able-bodied persons as well as those with disabilities, even though there is limited evidence associated with the benefits of PA in certain disability groups (6). It has been shown that only 38% of adults with a disability meet the international recommendations for PA compared to 49% in those without disability (7).…”
Section: Introductionmentioning
confidence: 99%
“…Although some interventions exist for the SCI/D population (eg, EatRight SCI 10 and Project Shake It Up 11 ), studies discuss important systems-level barriers, including a lack of targeted interventions for persons with SCI/D 12 and a lack of evidence-based guidelines on weight management in this population. 13 Providers may experience difficulty discussing weight concerns with patients; providers who also struggle with weight issues may be less likely to discuss weight management strategies with overweight/obese patients.…”
Section: Methodsmentioning
confidence: 99%